Gut bacteria facilitate pollinivory of the ladybird beetle Micraspis discolor - Li, Guannan; Huang, Yu-Hao; Cai, Li-Qun; Mou, Qian; Liang, Yuan-Sen; Sun, Yi-Fei; Li, Hao; Yang, Kun-Yu; Li, Hao-Sen; Pang, Hong (Frontiers in Microbiology, 2024)
The ladybird beetle Micraspis discolor plays an important role as a predator of various arthropods within Asia’s rice ecosystems. While pollen could serve as an alternative diet for this beetle, facilitating mass-rearing, its pollinivory might inadvertently result in attacks on crop pollen. This study aims to explore the role of gut bacteria on pollinivory of M. discolor. We found that antibiotic treatment significantly reduced the performance of M. discolor when fed Brassica campestris pollen. However, the treatment did not significantly affect their performance when fed an alternative diet of Ephestia kuehniella eggs. Further, we found that antibiotics can eliminate a strain of Serratia marcescens, SmMd, which is a specific gut bacterium in M. discolor. Moreover, the performance of M. discolor showed some degree of recovery when SmMd was reintroduced into its diet. Therefore, we propose that gut bacteria, particularly SmMd, play a significant role in pollen use by this ladybird beetle. This insight enhances our understanding of the important role of gut bacteria in insect adaptation to diverse diets and can potentially optimize the utilization of M. discolor in biological control strategies.